Personalized diagnostics through tumor profiling and circulating cell-free DNA : potential applications in colorectal cancer - Lau, Yi Ting (2014)
This study has been designed to assess the value of circulating cell-free DNA (ccf-DNA) as a personalized diagnostic tool for colorectal cancer (CRC). 26, 10, 14 and 11 somatic mutations were identified through exome capture sequencing pipelines, in the tumors of patient 019, 388, 239 and LHS respectively. Patient primary-specific primer (PPS-ctNA) pairs were designed for each variant. Multiplex PCR at optimized conditions, followed by amplicon sequencing was performed on the DNA extracted from plasma, tumor and matched-normal samples from the four CRC patients, using the customized PPS-ctNA pairs. In patient 019, 18 out of 22 calls made by exome sequencing pipelines have been validated through the amplicon sequencing analysis of tumor DNA. 8 out of 18 validated variants were found in the pre-op plasma and none was found in the post-op plasma. The findings suggest that it would be possible to develop a noninvasive blood test that has potential for personalized diagnosis and treatment and for screening of individuals at risk for dissemination and recurrence. However, further work is needed to standardize the conditions for multiplex PCR and sample analysis. Large prospective studies with continuous follow-ups are necessary to integrate ccf-DNA detection assays into the clinical setting.